Media sociology and journalism : studies in truth and democracy - Nielsen, Greg Marc, 1953- (Key issues in modern sociology., 2023)
While the alt right and post-truth attitudes render democracy fragile, so does professional journalism when it reports on the most vulnerable subjects in society but rarely addresses them as the imagined audience. A dialogical critique of divisions in news media, politics, and contemporary sociological theory can provide an alternative way forward.